Prosocial Behavior Can Moderate the Relationship Between Rumination and Mindfulness - Meng, Yao; Meng, Gang (Frontiers in Psychiatry, 2020)
Abstract Objective: Rumination, which is a coping style to distress has become a common mode of thinking about mental illnesses such as depression and anxiety. Improving mindfulness is an effective way to help people cope with rumination. Individuals who had higher prosocial behaviors reported a high level of mindfulness. This study aimed to explore whether prosocial behavior helps individuals with high-level rumination improve their mindfulness, and explain the reason why prosocial behavior can influence the relationship between mindfulness and rumination. Methods：Introducing prosocial behavior situations, the first study chose 51 high-level rumination and 53 low-level rumination participants and measured the influence of prosocial behavior on mindful attention awareness in the present moment. In the second study, a questionnaire was conducted among 261 participants to explore the moderating effect of prosocial behavior between rumination and mindfulness. Results：In individuals with high-level rumination, ΔMAAS (Mindful Attention Awareness Scale) (post test-baseline) scores in the prosocial behavior condition were significantly higher compared to those in the control condition (p=0.003). Meanwhile, prosocial behavior played a moderating effect between reflective pondering of rumination and mindfulness (R2=0.03, p=0.004). Conclusions：Encouraging prosocial behavior is an effective way to improve mindfulness in highly ruminative individuals.